(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Strengthening children’s spiritual immunity in preschool education, meaningful organization of their leisure time, engaging them in various fields of art, taking into account their interests and abilities, organizing a wide range of books, various sports, etc. Emphasis is placed on the development of reading skills, the formation of basic skills in various professions in various games and competitions.